Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1021/acscatal.1c01077
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Coupling of Ketone Enolates with Grignard and Zinc Reagents with First-Row Transition Metal Catalysts

Abstract: The stereoselective transformation of ketones to substituted olefins has become of great importance in organic synthesis. This Review helps to define the scope and limitations of the first-row transition metal-catalyzed cross-couplings between various enolates and aryl, heteroaryl, alkenyl, alkynyl, and alkyl Grignard and zinc reagents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 78 publications
(148 reference statements)
0
15
0
Order By: Relevance
“…In conclusion, we have developed an unprecedented catalyst‐controlled regiodivergent strategy for the transformation of challenging internal aliphatic PADs into structurally diverse 1,3‐dienyl and allyl esters with high regio‐ and stereoselectivity. This protocol allows for highly stereoselective access to a diverse range of valuable 1,3‐dienyl and alkenyl esters with latent functionalities for further synthetic elaboration [34] . The regioselectivity pattern can easily be manipulated by an appropriate selection of either ligand structure or metal catalyst source.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In conclusion, we have developed an unprecedented catalyst‐controlled regiodivergent strategy for the transformation of challenging internal aliphatic PADs into structurally diverse 1,3‐dienyl and allyl esters with high regio‐ and stereoselectivity. This protocol allows for highly stereoselective access to a diverse range of valuable 1,3‐dienyl and alkenyl esters with latent functionalities for further synthetic elaboration [34] . The regioselectivity pattern can easily be manipulated by an appropriate selection of either ligand structure or metal catalyst source.…”
Section: Discussionmentioning
confidence: 99%
“…This protocol allows for highly stereoselective access to a diverse range of valuable 1,3-dienyl and alkenyl esters with latent functionalities for further synthetic elaboration. [34] The regioselectivity pattern can easily be manipulated by an appropriate selection of either ligand structure or metal catalyst source. In this regard, depending on the choice of phosphine ligand backbone, two general approaches have been well established using the common palladium: 1) oxidative addition-reductive elimination pathway and 2) electrophilic palladium catalysis (π-Lewis acid activation) pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The diastereoconvergent reaction is highlighted in this report due to its synthetic utility, as it obviates the need for stereoselective starting material preparation, which is particularly challenging for the corresponding ( Z )-configured enol tosylates . An optimization study was designed using kraken , a computational database of descriptors for >1500 phosphorus ligands, to identify a diverse set of phosphines to evaluate, which enabled the identification of reaction conditions for a Ni-catalyzed Suzuki–Miyaura cross-coupling. The optimized conditions were then applied to the synthesis of a variety of tetrasubstituted alkene scaffolds in typically high diastereomeric ratios of up to ∼90:10 E / Z and Z / E . Notably, the unique mechanistic features of this catalytic transformation contrast with the thermodynamic control of previously developed convergent cross-couplings for the synthesis of di- and trisubstituted alkenes, which typically proceed via metal hydride catalyzed isomerizations. Our mechanistic hypothesis is supported by a combination of DFT calculations and experimental insights to shed insight into the elusive isomerization step that has previously been observed in several cross-coupling reactions of alkenyl electrophiles. ,, …”
Section: Introductionmentioning
confidence: 99%
“…59−61 Our mechanistic hypothesis is supported by a combination of DFT calculations and experimental insights to shed insight into the elusive isomerization step that has previously been observed in several cross-coupling reactions of alkenyl electrophiles. 49,56,62 ■ RESULTS AND DISCUSSION Optimization Studies. At the outset of the investigation, preliminary experimental data indicated that monophosphine ligands effectively promoted a nickel(0) cross-coupling of enol tosylate 1a and pinacol boronate 2a to access representative tetrasubstituted alkene diastereomers 3aa (Figure 3A, see Supporting Information for details).…”
Section: ■ Introductionmentioning
confidence: 99%